If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9(-11p + -16) = 7(15p + -3) + -5p Reorder the terms: -9(-16 + -11p) = 7(15p + -3) + -5p (-16 * -9 + -11p * -9) = 7(15p + -3) + -5p (144 + 99p) = 7(15p + -3) + -5p Reorder the terms: 144 + 99p = 7(-3 + 15p) + -5p 144 + 99p = (-3 * 7 + 15p * 7) + -5p 144 + 99p = (-21 + 105p) + -5p Combine like terms: 105p + -5p = 100p 144 + 99p = -21 + 100p Solving 144 + 99p = -21 + 100p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-100p' to each side of the equation. 144 + 99p + -100p = -21 + 100p + -100p Combine like terms: 99p + -100p = -1p 144 + -1p = -21 + 100p + -100p Combine like terms: 100p + -100p = 0 144 + -1p = -21 + 0 144 + -1p = -21 Add '-144' to each side of the equation. 144 + -144 + -1p = -21 + -144 Combine like terms: 144 + -144 = 0 0 + -1p = -21 + -144 -1p = -21 + -144 Combine like terms: -21 + -144 = -165 -1p = -165 Divide each side by '-1'. p = 165 Simplifying p = 165
| m+h=60 | | -5(-5x+2)+2(-8-8x)=28+10x | | f(x+h)=-x^2+x | | .3x=-.78 | | (Z-5)/7 | | -4x-2(-4x)=-28 | | X/10=18/36 | | h+60=m | | -8.8+3x-6.9+4x-2.8=5.6+8x+1.4 | | -9.6=u/3-2.1 | | 2y+8=7y+6 | | 83-2x=77 | | 7n-18=8n-5 | | 4(-20m+20)-12m=-8(-11m-10) | | 4x^2+20x=10 | | 2x-10x=-6-18 | | 137/12x=10 | | 6x-19=5x+14 | | -3(x+8)-(-4x-2)=3 | | 8r+12p-7-3p= | | -2(-13s-18)=20s-20-1s | | 4.76=0.75x+0.25 | | X+3x+16x=180 | | 112/10x=10 | | 4x-(7x+21)=-15 | | 112x=10 | | 17+9(-5u+16)=-16u-9-19u | | 3a+5b=100 | | 2.1-0.9+0.9z-0.7z+0.2z+x^2-0.2z^2= | | -5(-20j-17)=-11+4j | | 8x+7(-6x-17)=-17 | | -5(2+4v)=-2(-10+15v) |